Taysir method of teaching halal and haram to indigenous people (Orang Asli) in Malaysia-A preliminary study - Mohd Zohdi Mohd Amin; Yasmin Hanani Mohd Safian; Mohd Nasir Abd Majid; Wan Azura Wan Ahmad; Mohd Azhar Ibrahim Residi; Adnan Mohamed Yusoff; Mohammed Akhiruddin Ibrahim; Khalid, Muhammad Yusuf; Arifin, Mohd Syakir (American Scientific Publishers, 2024)
Indexed by SCOPUS